COMPARATIVE STUDIES ON COOPERATIVE STOCHASTIC DIFFERENTIAL GAME AND DYNAMIC SEQUENTIAL GAME OF ECONOMIC MATURITY - DAI, Darong; YIN, Jun (Theoretical and Practical Research in Economic Fields, 2013)
In the paper, we are encouraged to investigate the effect of game structure imposed on the minimum-time needed to economic maturity in a dynamic macroeconomic model. Indeed, we have established a basic framework for the comparative study of the cooperative stochastic differential game and dynamic sequential game of economic maturity. Moreover, in a simple stochastic growth model, closed-form solution of the minimum-time needed to economic maturity has been derived with the explicit condition, under which it is confirmed that cooperation between the representative household and the self-interested politician will definitely lead us to much faster economic maturity than that of sequential action, supplied, too. Finally, our model supports the comparative study of the minimum-time needed to economic maturity under different political-institution constraints.